Features of the sexual life during pregnancy - ISAJEVA, Jelena; ŠILKŪNAS, Mindaugas; DRĄSUTIENĖ, Gražina Stanislava; BARTKEVIČIENĖ, Daiva (Acta medica Lituanica, 2012)
Background. The aim of our study was to evaluate Vilnius and Vilnius Region women’s knowledge about sexual intercourse during pregnancy.Materials and methods. The study included 94 women who were in the Center Affiliate of VUH Santariskiu Clinics after delivery. The women were interviewed using a questionnaire. They were divided in three groups by levels of education.Results. The study showed that 83% of pregnant women had sexual intercourse during pregnancy. 55.1% had coitus several times a month. The first trimester was the most frequent period of sexual intercourse (52.6%). 22.6% of pregnant women were at high risk of miscarriage and 61.9% of them have had sexual intercourse. The frequency of miscarriage in the sexually active group was 17.9% and in the non-active group it was 50% (p < 0.05). All women who reported frequent sexual intercourse were not at threat for miscarriage compared to incidence of miscarriage of those 13 (22%) women who reported infrequent intercourse (p = 0.019). 79.8% of pregnant women were concerned about the adverse effects of sexual intercourse on pregnancy outcomes. 20.2% of the women thought that intercourse during pregnancy was safe. 63.8% of pregnant women were not asked by doctors during pregnancy about their sexual life.Conclusions. The majority (79.8%) of pregnant women were concerned about the adverse effects of sexual intercourse on pregnancy outcomes but even 83% of pregnant women had sexual intercourse during pregnancy. There were no statistical differences between women with different education level. Pregnant women were rarely asked by doctors about their sexual life.